Environmental temperature and its effect on physiological parameters in Nellore cows and crosses under conditions of the Peruvian tropics - Unchupaico P., Ide (2020)
The aim of this study was to determine the physiological parameters related to body thermoregulation, as well as basic haematological parameters between Nellore cows and crossbreeds under heat stress. The study was carried out in the province of Satipo, Junín region, Peru, at 628 meters above sea level. Sixteen crossbred cows (Brown Swiss x Nellore) and 16 Nellore cows were used. The physiological parameters (body temperature, respiratory rate and heart rate) were evaluated in the morning (06:00-07:00) and in the afternoon (14:00-17:00). Blood samples were taken to determine haemoglobin (g/dl), haematocrit (%), mean corpuscular volume (MCV, fl), mean corpuscular haemoglobin (MCH, pg), mean corpuscular haemoglobin concentration (MCHC, g/dl). Thermoregulatory functions (rectal temperature, heart rate and respiratory rate) were affected during hours of heat stress in both racial groups (p<0.05). Haematological values were found within the referential ranges, except the MCV and MCH.